Typification of three accepted names in Limonium (Plumbaginaceae) - Vallariello, Roberta; Iamonico, Duilio; Guacchio, Emanuele Del (Phytotaxa, 2016)
The names Statice cumana (currently Limonium cumanum), S. inarimensis (≡ L. inarimensis), and S. remotispicula (≡ L. remotispiculum) are lectotypified on specimens preserved at NAP and FI. These species are endemic to the south Tyrrhenian coasts (SW Italy), two of them (L. cumanum, and L. inarimensis) being narrow endemic to Campania region. A nomenclatural change (Limonium cumanum var. glabrescens, comb. nov.) is also proposed.